A cognição judicial imparcial e os efeitos dos vieses cognitivos no processo penal democrático - Hebert Soares Leite (2020)
This paper aims to understand the principle of impartiality in Brazilian Criminal Procedural Law, based on the studies of cognitive behavioral psychology, more precisely the theory of cognitive dissonance, cognitive biases and the dual-system theory: fast and slow. Therefore, the theme was developed in six chapters. Initially, an overview of the Constitutional Model of the Democratic Criminal Procedure was outlined, by revisiting the characteristics of the classic, inquisitorial, mixed and democratic accusatory systems of justice. Subsequently, impartiality in the context of criminal procedural systems was analyzed as an essential support of a democratic process, its due conceptualization, dimension and importance for the Rule of Law, as well as the fallacy of the concept of judicial neutrality. In third and fourth chapters, as the main object of the research, it went deeper into the study of cognitive behavioral psychology, the systems S1 - automatic - and S2 – deliberative, the theory of cognitive dissonance, heuristics and biases. In the fifth chapter, in order to demonstrate and to prove the influence of cognitive dissonances and cognitive biases in judicial decision-making, the results of the researches developed by Schünemman and Gloeckner are presented. Finally, the proposals for debiasing brought by Legislation 13.964/2019 is analyzed.